2019
DOI: 10.1051/epjap/2019190239
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field impact on nanofluid convective flow in a vented trapezoidal cavity using Buongiorno's mathematical model

Abstract: Numerical study for the effect of an external magnetic field on the mixed convection of Al2O3–water Newtonian nanofluid in a right-angle vented trapezoidal cavity was performed using the finite volume method. The non-homogeneous Buongiorno model is applied for numerical description of the dynamic phenomena inside the cavity. The nanofluid, with low temperature and high concentration, enters the cavity through the upper open border, and is evacuated through opening placed at the right end of the bottom wall. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 38 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…To show the effectiveness of nanofluid, lid-driven cavities a good choice to achieve that. As a result, many of researchers investigated the mixed convection in cavities utilize nanofluid or non-Newtonian according to cavity geometry in the recent years [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To show the effectiveness of nanofluid, lid-driven cavities a good choice to achieve that. As a result, many of researchers investigated the mixed convection in cavities utilize nanofluid or non-Newtonian according to cavity geometry in the recent years [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…To show the effectiveness of nanofluid, lid-driven cavities a good choice to achieve that. As a result, many of researchers investigated the mixed convection in cavities utilize nanofluid or non-Newtonian according to cavity geometry in the recent years [19,20,21,22,23,24,25]. Kahveci et al (2016), [26] presented the effect of viscosity models of CuO nanofluid in mixed convection lid-driven cavity during constant heat flux.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been offered to improve the HT with vented cavities, such as using fins [25,26], rotating objects [27,28], flow pulsations [29,30], magnetic fields [31], and elastic walls [32]. Nanofluids have also been considered in vented cavities and in convection studies [33][34][35][36][37][38], and their effectiveness has been shown.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, many advancements and modeling improvements have been achieved to simulate the nanofluid behavior and asses their improvements in diverse thermal systems (Kakaç and Pramuanjaroenkij, 2009;Sajid and Ali, 2019;Ismael et al, 2016;Mehryan et al, 2020;Esfe et al, 2020;Chamkha et al, 2015;Darbari and Rashidi, 2021;Mohebbi and Rashidi, 2017;Mehryan et al, 2017). The effectiveness of using nanofluids in VeC systems has been shown in many studies (Jasim et al, 2021;Benzema et al, 2019;Kalidasan and Kanna, 2016;Selimefendigil and Öztop, 2019;Ahmed, 2020). Depending upon the port locations, operating conditions and nanofluid types, different improvement HFF 32,11 amounts have been reported.…”
mentioning
confidence: 99%